Application of textile fibres from tire recycling in asphalt mixtures. Issue 10 (3rd October 2022) - Pais, Jorge C.; Santos, Caio R. G.; Lo Presti, Davide
Abstract : The tire rubber obtained from end-of-life car and truck tires has been successfully recycled, among other applications, in the asphalt industry by providing a mean to get asphalt mixtures with superior performance. Textile fibres are another component derived from tire recycling typically disposed of in landfills or used in energetic valorisation. This paper wants to re-ignite interest in this secondary product by evaluating its use as a valuable resource in asphalt mixtures. Indirect tensile tests, dynamic modulus, fatigue resistance, and permanent deformation tests were performed on a series of AC14 asphalt mixtures manufactured with two binders, namely 50/70 and 35/50 pen, using several binder and fibre contents. The results indicate that incorporating fibres of tire recycling is not problem-free. Results have shown that can be advisable in pavement applications whenever the investigated fibre-modified mixtures allowed to incorporate at least 6.5% binder content with great benefit for pavement performance.